Stages of transtheoretical model among college smoker in Selangor - Zainal Abidin, Muhammad 'Adil; Kadir@Shahar, Hayati; Abdul Manaf, Rosliza (2018)
Background of study: Tobacco smoking continue to be the leading causes of premature death in Malaysia for the last 3 decades. The national prevalence of smoking among the young adult is low compare to other age group. However, the percentage of quit attempt among young adult are among the highest. The aim of this study is to determine the prevalence and pattern of various stages of smoking cessation among college students using the Transtheoretical model (TTM) in order to provide basis for stage based intervention.